1995
DOI: 10.1080/01904169509365021
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, chlorophyll fluorescence and soluble carbohydrates in sunflower leaves as affected by boron deficiency

Abstract: The effect of various boron levels in the nutrient solution on the growth, boron and chlorophyll content, photosynthesis and chlorophyll fluorescence in the leaves of young sunflower (Helianthus annuus L.) plants was studied under greenhouse conditions. Deficiency of boron decreased the dry matter yield of the roots, shoots and leaves. The content of boron in all analyzed plant parts increased with the increase of boron levels in the nutrient solution, more so in the shoots than in the roots. Leaf area was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 14 publications
6
27
0
Order By: Relevance
“…Liu (2000) found that B enhanced photosynthesis efficiency of soybean by membrane maintenance and photosynthesis products translocation and Mo did by chlorophyll stability and enlarging leaf area for photosynthesis. Some studies demonstrated that B excess or deficiency resulted in a decrease of photosynthesis rates in Cucurbita pepo, citrus and sunflower leaves (Lovatt and Bates 1984, Kastori et al 1995, Papadakis et al 2004), but Sage et al (1989) reported that photosynthesis in Streptanthus morrisonii leaves are unaffected by high boron and Zhao and Oosterhuis (2003) found that in the field study, neither soil nor foliar B treatment improved cotton photosynthesis due to sufficient soil B for plant growth (0.2 and 0.3 mg/kg at two study sites). Gupta et al (1991) also observed that treatment with 2 mg/kg Mo (soil dry weight) resulted in a decrease in photosynthesis of 22% in the soybean leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Liu (2000) found that B enhanced photosynthesis efficiency of soybean by membrane maintenance and photosynthesis products translocation and Mo did by chlorophyll stability and enlarging leaf area for photosynthesis. Some studies demonstrated that B excess or deficiency resulted in a decrease of photosynthesis rates in Cucurbita pepo, citrus and sunflower leaves (Lovatt and Bates 1984, Kastori et al 1995, Papadakis et al 2004), but Sage et al (1989) reported that photosynthesis in Streptanthus morrisonii leaves are unaffected by high boron and Zhao and Oosterhuis (2003) found that in the field study, neither soil nor foliar B treatment improved cotton photosynthesis due to sufficient soil B for plant growth (0.2 and 0.3 mg/kg at two study sites). Gupta et al (1991) also observed that treatment with 2 mg/kg Mo (soil dry weight) resulted in a decrease in photosynthesis of 22% in the soybean leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that B deficiency decreases plant photosynthetic capacity (Kastori et al, 1995;Oosterhuis, 2002, 2003). In mustard (Brassica campestris), decreased rate of CO 2 assimilation appears to result from both decreased Hill reaction activity and low intercellular CO 2 concentration (Sharma and Ramchandra, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…Valores seguidos pela mesma letra indicam não significância a 5% pelo teste de Tukey. Reductions in the synthesis of sugars were also observed by Kastori et al (1995) in B-deficient sunflower leaves, which were explained as a decrease in their ability to assimilate O 2 and CO 2 . Due to damage caused to the photosynthetic process, starches and sugars were accumulated for a short period in leaves submitted to B deficiency, indicating a reduction in the translocation of photosynthates in sink organs.…”
Section: Resultsmentioning
confidence: 94%